Low levels of arsenic exposure during pregnancy and maternal and neonatal thyroid hormone parameters: The determinants for these associations - Chunmei Liang; Yan Han; Liya Ma; Xiaoyan Wu; Kun Huang; Shuangqin Yan; Zhijuan Li; Xun Xia; Weijun Pan; Jie Sheng; Qunan Wang; Shilu Tong; et al. (Environment International, 2020)
Background: The potential maternal and neonatal thyrotoxicity associated with exposure to arsenic during pregnancy is very limited and unclear. Objectives: This study aimed to examine the associations between arsenic exposure levels in maternal and cord serum and maternal and neonatal thyroid hormone parameters in a prospective birth cohort study. Methods: The study including 2089 mother-neonate pairs was based upon Ma’an Shan birth cohort study in China. The exposure variables including maternal serum arsenic levels in the first, second and third trimester and average arsenic exposure level during pregnancy and cord serum arsenic level. Maternal serum TSH and FT4 levels in the first, second and third trimester and cord serum TSH and FT4 levels were determined using the electrochemiluminescence immunoassay with Cobas Elecsys 411. Linear mixed models were used to examine associations between arsenic exposure variables during pregnancy and maternal thyroid hormone parameters, and multiple linear regression analyses were used to examine associations between arsenic exposure during pregnancy and neonatal thyroid hormone parameters. Bayesian kernal machine regression (BKMR) analyses based on a kernel function were also used to examine the effects of exposure to metal mixtures (arsenic, mercury, cadmium and selenium). Results: The geometric means of arsenic exposure levels across 3 trimesters were 1.74 μg/L, 1.81 μg/L and 1.99 μg/L, respectively, and 1.90 μg/L in cord serum; the geometric means of maternal FT4 levels across 3 trimesters were 16.91 pmol/L, 11.91 pmol/L and 13.16 pmol/L, respectively, and 16.10 pmol/L in cord serum; the geometric means of maternal TSH levels across 3 trimesters were 1.27 μIU/mL, 2.32 μIU/mL and 2.08 μIU/mL, respectively, and 8.47 μIU/mL in cord serum. Maternal serum arsenic levels in the first, seond, third trimester and average arsenic exposure level during pregnancy were all not associated with maternal thyroid hormone parameters after adjustment for all the covariates, the adjusted β (95% CI) were −0.002 (−0.10 to 0.09), 0.05 (−0.05 to 0.16), −0.09 (−0.17 to 0.003) and −0.05 (−0.22 to 0.11) for maternal FT4, respectively; and −0.005 (−0.04 to 0.03), −0.003 (−0.04 to 0.03), −0.004 (−0.03 to 0.02) and −0.01 (−0.06 to 0.04) for maternal lnTSH, respectively. Maternal serum arsenic levels in the first, second trimester and average arsenic exposure level during pregnancy were all inversely associated with neonatal FT4 level after adjustment for all the confounders, the adjusted β (95% CI) were −0.19 (−0.31 to −0.07), −0.14 (−0.26 to −0.01), −0.22 (−0.42 to −0.02), respectively; and cord serum arsenic level was positively related with neonatal TSH level, the adjusted β (95% CI) were 0.04 (0.001 to 0.08). The adverse joint toxic effect of the four metals in maternal serum in the first trimester and in cord serum on neonatal thyroid hormone parameters were also found. Conclusions: In this study, exposure to low levels of arsenic during pregnancy could directly affect neonatal thyroid hormone parameters without being mediated by maternal effect of exposure, and maternal serum arsenic levels in the first, second trimester and average arsenic exposure level during pregnancy and cord serum arsenic level may be risk factors affecting neonatal thyroid hormones. These findings indicate that neonates are more sensitive to the thyrotoxicity of arsenic exposure even at low levels. In addition, the adverse joint toxic effect of metal mixtures is also worthy of attention.